On the Importance of 'Positive Identity' to Transformative Education - Boaz Tsabar (European Teacher Education Network, 2016)
The article seeks to highlight the fundamental importance of positive concept of identity to transformative education. The paper will claim that critical education needs to address the complex dialectical nature of identity - its immanent tensions between the individual and the collective and between liberation and empowerment. The paper will also argue that radical postmodern concept of identity can lead to suppression of identity and the reduction of humanity. Through its critical examination this article hopes to re-establish the dialectical nature of positive identity and its importance for urban education.